The effect of Visual Aesthetic and Endorser Type on Attitude Toward Advertising, Attitude Toward Product, and Purchase Intention Vegan Food - Gozali, Nidia Artanti; Mardhiyah, Dien; Futuwwah, Ali Imaduddin; Yusvianty, Riedha Sabila Ardian (Universitas Airlangga, 2024)
Objective: The COVID-19 pandemic has encouraged people to adopt healthier lifestyles, yet available information remains scarce. Marketers often utilize advertising to educate the public, but ads must be engaging to capture attention. Therefore, this study seeks to examine how the content and sources of advertisements influence attitudes toward vegan food using the S-O-R Theory. Design/Methods/Approach: This study conducts experiments on social media apps, manipulating vegan food ads across different designs and endorsers using a 2x2 factorial design between subjects with 160 participants. It utilizes vegan meat as a stimulus and conducts manipulation checks before distributing questionnaires. Findings: The findings indicate that classical aesthetics are more effective in shaping attitudes toward vegan food advertising. Consumers purchase vegan food to maintain their health, and by using classical aesthetics, consumers perceive the food as healthier. Originality/Value: Previous research on vegan food has focused on various aspects such as values, claims, motivation, and ideologies. In contrast, this study explores how vegan food ads positively influence consumer attitudes, with unique visual aesthetics findings in these advertisements. Practical/Policy Implication: Marketers must focus on visual aesthetics and choose suitable endorsers for effective vegan food ads, shaping positive consumer attitudes and purchase intentions.